2019
DOI: 10.3390/ijerph16183397
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Health Literacy among School-Aged Children: First Evidence from Lithuania

Abstract: Health literacy as a set of competencies to promote and sustain health has received significant research attention, particularly in studies on adults. Improving health literacy at an early age is crucial to personal health and development, so there is a need to investigate the health literacy of school-aged children. The aims of this study were to determine the level of subjective health literacy among adolescents in Lithuania and to examine the association between health literacy, school achievement, health e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 39 publications
6
47
2
13
Order By: Relevance
“…Consistent with existing theoretical frameworks [1,44], we found that adolescent health literacy was related to intrapersonal, interpersonal and environmental factors. Additionally, our findings are in line with previous empirical findings which suggested a close relationship between health literacy and personal self-efficacy [45], social support [46] and school environment [47]. Compared to previous quantitative studies [45][46][47], we did not analyse the relationship between health literacy and its antecedents separately.…”
Section: A Holistic Approach To Improving Adolescent Health Literacysupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with existing theoretical frameworks [1,44], we found that adolescent health literacy was related to intrapersonal, interpersonal and environmental factors. Additionally, our findings are in line with previous empirical findings which suggested a close relationship between health literacy and personal self-efficacy [45], social support [46] and school environment [47]. Compared to previous quantitative studies [45][46][47], we did not analyse the relationship between health literacy and its antecedents separately.…”
Section: A Holistic Approach To Improving Adolescent Health Literacysupporting
confidence: 88%
“…Additionally, our findings are in line with previous empirical findings which suggested a close relationship between health literacy and personal self-efficacy [45], social support [46] and school environment [47]. Compared to previous quantitative studies [45][46][47], we did not analyse the relationship between health literacy and its antecedents separately. Instead, we considered all these antecedents together based on Manganello's health literacy framework [1].…”
Section: A Holistic Approach To Improving Adolescent Health Literacysupporting
confidence: 88%
“…In the current study, we asked the respondents to answer the questions in light of the current pandemic situation. The HLSAC scale was originally validated for adolescents in seventh and ninth grades but it has also been applied in studies on older adolescents [13,15,16]. The scale was not previously properly validated in Norwegian; hence, we conducted exploratory factor analysis, which identified a dominant first factor with eigenvalue = 3.88.…”
Section: Plos Onementioning
confidence: 99%
“…Fretian et al [68] consider the measurement of health literacy in children in "Exploring Associated Factors of Subjective Health Literacy in School-Aged Children in Germany". Sukys et al [69] similarly consider this issue in the context of an understudied population in "Subjective Health Literacy among School-Aged Children: First Evidence from Lithuania". Parents are shown to be key to health literacy in young people in "How Did Parents View the Impact of the Curriculum-Based HealthLit4Kids Program Beyond the Classroom?"…”
Section: Organizational Level: Schools Students and Adolescentsmentioning
confidence: 99%